Rancang Bangun Robot Pengantar Obat dan Makanan Pasien Berbasis Internet of Things - Edy Sopyan; Dedi Suarna; Muhammad Harun Ashar; Mustakim (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The rapid development of technology today, especially in the field of information technology, requires everyone to be able to follow it so as not to be left behind by other developing countries, especially regarding the use of technology. The goal to be achieved from this research is to design a robot that can ease the work of medical personnel, especially in delivering medicine and food to patients so that they no longer need to deliver it manually, just use a robot controlled by an application. The research method used is the waterfall method. Robot testing is done by testing the control distance to find out how far the robot can be controlled. This robot consists of 3 layers and has 4 wheels. The working system of this robot is controlled by 4 buttons namely forward, backward, left and right by the user through a control application. The command is sent to the NodeMcu Esp8266 which is then forwarded to the Motor Driver L298n as the overall voltage of the system is made to work properly.